Implications of feed concentrate reduction in organic grassland-based dairy systems: a long-term on-farm study. (24th April 2017) - Leiber, F.; Schenk, I. K.; Maeschli, A.; Ivemeyer, S.; Zeitz, J. O.; Moakes, S.; Klocke, P.; Staehli, P.; Notz, C.; Walkenhorst, M.
Abstract : In response to increasing efforts for reducing concentrate inputs to organic dairy production in grassland-rich areas of Europe, a long-term study was conducted, which assessed the impacts of concentrate reductions on cows' performance, health, fertility and average herd age. In total, 42 Swiss commercial organic dairy cattle farms were monitored over 6 years ('Y0', 2008/09 until 'Y5', 2013/14). In comparison with overall data of Swiss herdbooks (including conventional and organic farms), the herds involved in the project had lower milk yields, similar milk solids, shorter calving intervals and higher average lactation numbers. During the first 3 project years farmers reduced the concentrate proportion (i.e. cereals, oilseeds and grain legumes) in the dairy cows' diets to varying degrees. In Y0, farms fed between 0% and 6% (dietary dry matter proportion per year) of concentrates. During the course of the study they changed the quantity of concentrates to voluntarily chosen degrees. Retrospectively, farms were clustered into five farm groups: Group '0-conc' ( n =6 farms) already fed zero concentrates in Y0 and stayed at this level. Group 'Dec-to0' ( n =11) reduced concentrates to 0 during the project period. Groups 'Dec-strong' ( n =8) and 'Dec-slight' ( n =12) decreased concentrate amounts by >50% and <50%, respectively. Group 'Const-conc' ( n =5 farms) remained at the initial level of concentrates during the project. Milk recording data were summarised and analysed per farm and project year. Lactation number and calving intervals were obtained from the databases of the Swiss breeders' associations. Dietary concentrate amounts and records of veterinary treatments were obtained from the obligatory farm documentations. Data were analysed with GLMs. Daily milk yields differed significantly between farm groups already in Y0, being lowest in groups 0-conc (16.0 kg) and Dec-to0 (16.7 kg), and highest in groups Dec-slight (19.6 kg) and Const-conc (19.2 kg). Milk yield decreases across the years within groups were not significant, but urea contents in milk decreased significantly during the course of the project. Milk protein, somatic cell score, fat–protein ratio, average lactation number, calving interval and frequency of veterinary treatments did not differ by group and year. In conclusion, 5 years of concentrate reduction in low-input Swiss organic dairy farms, affected neither milk composition, nor fertility and veterinary treatments. Milk yields tended to decline, but at a low rate per saved kilogram of concentrate.